Analysis of soil quality through aerial biomass contribution of three forest species in relict high Andean forests of Peru - Zanabria Cáceres, Ysaias Timoteo (2024)
The biomass that accumulates on the forest floor and its subsequent decomposition play an important role in maintaining the productivity of different terrestrial ecosystems by constituting the main nutrient flow to the soil. The objective of the study focused on analyzing the nutrient contribution to the soil derived from the aboveground biomass of three native forest species in relict forests of the Central Peruvian Sierra with socioeconomic and environmental relevance. Using random delineation methods, soil samples were collected at 20-30 cm depth, which were subjected to physical, chemical, and biological analyses, developing the determination of a Soil Quality Index (SQI). The results highlight that forests of Polylepis racemosa and Alnus acuminata significantly exhibit a higher SQI, with values of 0.66 and 0.58, respectively, compared to Escallonia resinosa, with the forestless system being of lower quality with an SQI of 0.28. The relict forests, Dorado, Colpar, and Talhuis, presented the highest SQIs (0.53, 0.52, and 0.48), while Saño obtained the lowest SQI with 0.39, with no significant differences among them. The forests of Polylepis racemosa and Alnus acuminata showed a superior soil structure, higher organic matter content, moisture retention, and microbial biomass compared to other analyzed systems.